Looking for JJ - Cassidy, Anne, 1952- (London : Scholastic, 2013)
Seventeen-year-old Alice, released from prison with a new identity after serving six years for murdering a child, tries to keep her anonymity from the British tabloids, while haunted by memories of her past trauma.
Young Adult.
Young Adult
Keywords: Child abuse -- Fiction; Emotional problems -- Fiction; Identity -- Fiction; Murder -- Fiction; Child abuse -- Fiction; Emotional problems -- Fiction; Homicide -- Fiction; Identity -- Fiction; England -- Fiction; England -- Fiction